ANALISIS EKONOMI POLITIK KRISIS ENERGI GLOBAL TERHADAP KEBIJAKAN SUBSIDI ENERGI DI INDONESIA - Rizky Amelia Siregar; Hanifa Ayu S; Ahmad Zaki Sinulingga; Reni Ria Armayani Hasibuan (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The ongoing global energy crisis from 2022 to 2025 has significantly affected the economic and political stability of developing countries, including Indonesia. The fluctuation of oil, natural gas, and coal prices due to geopolitical conflicts and global energy transition has placed strong pressure on Indonesia’s national energy subsidy policy. This study aims to analyze how the global energy crisis influences Indonesia’s energy subsidy policy through a political economy perspective. A qualitative descriptive approach was applied using document and policy discourse analysis, drawing on sources such as Indonesia’s 2025 State Budget Financial Note, reports from the International Energy Agency (IEA), the World Bank, and various government statements. The findings reveal that Indonesia’s energy subsidy policy is not merely economically driven but is also shaped by complex political considerations aimed at maintaining social stability and regime legitimacy. The government utilizes energy subsidies as a political instrument to preserve public trust amid fiscal pressures resulting from global energy price volatility. This study contributes theoretically by strengthening the understanding of energy subsidies as a politicaleconomic instrument, and practically by providing policy recommendations for a more transparent, gradual, and sustainable energy subsidy reform aligned with Indonesia’s energy transition goals.